2021
DOI: 10.1002/ird.2594
|View full text |Cite
|
Sign up to set email alerts
|

Surface water quality classification using data mining approaches: Irrigation along the Aladag River*

Abstract: Knowledge of water quality is an important requirement in planning, developing, and protecting water resources. Therefore, it is essential to determine the quality of water for various uses, including irrigation in different areas. The aim of this study is to evaluate the performance of different data mining methods using water quality parameters measured in Aladag River. At the first stage, the water quality in the Aladag River in Turkey was classified by United States Salinity Laboratory (USSL) diagrams and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many studies explain that artificial neural network (ANN), adaptive neuro fuzzy inference system (ANFIS) and other machine learning methods can outperform traditional computational methods to predict evaporation and evapotranspiration to explain the effect on agricultural water use (Adeloye et al, 2012;Kisi et al, 2015;Abrishami et al, 2018;Sanikhani et al, 2019;Yamac and Todorovic, 2020;Elbeltagi et al, 2020;Petković et al, 2020;Yamaç, 2021;Sattari et al, 2021). AlMukhtar (2021) and Goyal et al (2014) did this for this purpose and predicted E with high accuracy with these models and performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies explain that artificial neural network (ANN), adaptive neuro fuzzy inference system (ANFIS) and other machine learning methods can outperform traditional computational methods to predict evaporation and evapotranspiration to explain the effect on agricultural water use (Adeloye et al, 2012;Kisi et al, 2015;Abrishami et al, 2018;Sanikhani et al, 2019;Yamac and Todorovic, 2020;Elbeltagi et al, 2020;Petković et al, 2020;Yamaç, 2021;Sattari et al, 2021). AlMukhtar (2021) and Goyal et al (2014) did this for this purpose and predicted E with high accuracy with these models and performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that the most effective parameter in the probabilistic scenarios created for the model is the average temperature. Through scientific studies, it has been demonstrated that the maximum, minimum and average temperatures are more successful than other climate parameters in estimating evapotranspiration using artificial intelligence models (Abyaneh et al, 2011;Tabari et al, 2013;Aghajanloo et al, 2013;Yamaç and Todorovic, 2020;Sattari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this method falls short of providing decision-makers with instant insights and a comprehensive comprehension of groundwater quality, especially when multiple factors contributing to the deterioration of water quality are identified. To address this limitation, various computer-assisted plotting techniques like Piper, Durov, Schofield, Wilcox, and United States Salinity Laboratory (USSL) approaches have been involved in assessing the appropriateness of groundwater for agricultural watering [10][11][12][13][14][15][16][17]. Furthermore, Integrated Irrigation Groundwater Quality Indices (IIGWQIs) are derived from water's chemical composition and offer an effective means of evaluating water suitability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Integrated Irrigation Groundwater Quality Indices (IIGWQIs) are derived from water's chemical composition and offer an effective means of evaluating water suitability. By amalgamating several pivotal water quality indicators into a single value, these indices are designed to facilitate water quality management decisions for stakeholders [10,11,15,[18][19][20][21]. In the context of agriculture, these IIGWQIs are typically evaluated using a range of indices and variables [15,18,19].…”
Section: Introductionmentioning
confidence: 99%